N. V. MASLIUK: LEXICOGRAPHICAL ANALYSIS OF SYNCRETIC CONJUNCTIVES (ON THE MATERIAL OF THE «DICTIONARY OF THE UKRAINIAN LANGUAGE» IN 11 VOLUMES AND THE «DICTIONARY OF THE UKRAINIAN LANGUAGE» EDITED BY B. GRINCHENKO) - MASLIUK, N. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
complex sentences and structural semantic (semantic-syntactic) features of conjunctives. Dictionaries serve as a factual basis for the selection of language units, necessary for the study of transformational processes in the language system. Purpose. The purpose of the research is to find out the grammatical specifics of syncretic conjunctives on the material of lexicographic sources. Methods. To achieve the goal techniques of lexicographical method are used: continuous sampling, lexicographic analysis, quantitative elements analysis. Results. Comparative lexicographic analysis made it possible to clarify grammatical characteristics of syncretic conjunctives in the aspect of transitions. The part-of-speech potential of 14 subordinate-coordinate conjunctives on the material of two lexicographical sources – «Dictionary Ukrainian language» in 11 volumes and «Dictionary of the Ukrainian language» edited by B. Hrinchenko. Linguistic units and syntactic structures, widely represented in contemporary (late ХІХ – early ХХ century) speech, are the object of comparative analysis with modern manifestations of part-of-speech and syntactic variability of conjunctives. Out of the 14 subordinate-coordinate conjunctives (according to modern typology) partially coincidences in the determination of part-of-speech affiliation have 12 units that are 86 % of the total. In the «Dictionary» edited by B. Hrinchenko 11 are defined as conjunctions and 1 as an adverb. There are no matches in 14 % of conjunctives. Conjunctions себто /цебто are related to the pronouns сей / цей, and отже і / отже й qualified as an adverb in the «Dictionary» edited by B. Hrinchenko. Comparative analysis of subordinate-coordinate conjunctions that have coincidences in determination of part-of-speech affiliation, gives grounds to draw conclusions about imperfection of the system of differentiation of both notional and functional words for classes in the «Dictionary of the Ukrainian language» edited by B. Hrinchenko. Often illustrative material presents the use of a conjuction in the role of particle, and it is not correlated with this part of speech. «Dictionary» for edited by B. Hrinchenko contains many phonetic variants of pronunciation established in the modern Ukrainian language of conjunctions, but they are not recorded in the «Dictionary Ukrainian language» in 11 vols. Originality. The originality of scientific intelligence lies in the definition part-of-speech potential of syncretic subordinate-coordinate conjunctions on materials of the analyzed lexicographical works. Conclusion. It is concluded that lexicographical comparative analysis revealed differences in the formal expression of conjunctions in general and the definition of the grammatical paradigm of conjunctives in the syncretic composite sentences in particular. In the «Dictionary of the Ukrainian language» edited by B. Hrinchenko preference is given to word-forming, etymological and semantic approaches in the definition of part-of-speech affiliation of most of the analyzed language units, instead their syntactic role and position in the sentence are seldom taken into account. Offered in Dictionary articles, illustrative material widely represents options of the use of syncretic units in language, from the point of view of modern grammar allows finding out other syntactic positions of a word, to determine morphological characteristics of affiliation to another part of speech, which is reflected in dictionary articles «Dictionary of the Ukrainian language» in 11 volumes. The use of comparative lexicographical analysis demonstrates the dynamics of language processes, allows the fixation of the phenomena of transition through the formal-syntactic and semantic-syntactic approaches. The prospect of research is seen in a detailed lexicographical analysis of other syncretic conjunctives.